Tourist Satisfaction and Performance of Tourism Industries : How The Role of Innovative Work Behaviour, Organizational Citizenship Behaviour? - Purwanto, Agus; Novitasari, Dewiana; Asbari, Masduki (Journal of Industrial Engineering & Management Research, 2022)
The purpose of this research is to analyze the relationship between innovative work behaviour on satisfaction, innovative work behaviour on job performance, organizational citizenship behaviour on job performance, organizational citizenship behaviour on job satisfaction, innovative work behaviour on job performance through job satisfaction, organizational citizenship behaviour on job performance through job satisfaction. This study uses quantitative methods to test and prove the hypotheses that have been made through various tests and data processing. The number of samples in this study is the first 210 respondents of tourism industry in Banten, Indonesia.Based on data analysis by SmartPLS shows innovative work behaviour has significant effect on satisfaction, innovative work behaviour has significant effect on performance, organizational citizenship behaviour has significant effect on satisfaction, organizational citizenship behaviour has significant effect on performance, innovative work behaviour has significant effect on job performance through satisfaction, organizational citizenship behaviour has significant effect on performance through satisfaction.